EVALUATION OF LOWER GASTROINTESTINAL BLEEDING RISK ASSOCIATED WITH USE OF LOW DOSE ASPIRIN - AZIZ, MF; KHAN, AR; BASHIR, A (Biological and Clinical Sciences Research Journal, 2022)
To evaluate risk of aspirin related lower gastrointestinal bleeding a Prospective study was performed at Department of medicine, Nishtar Hospital, Multan from July 2019 to January 2020. Total 372 patients using low dose aspirin were selected from out-patient department of Medicine. All patients underwent diagnostic laboratory test for stool examination. A consultant pathologist confirmed presence or absence of lower gastrointestinal bleeding. Data including age, gender, history of bleeding per rectum, blood on stools, BMI, duration of aspirin use, and reason for aspirin prescription was recorded. The study was conducted on 372 patients, 120 (32.3%) were female while 252 (67.7 %) were male. Mean age of the patients was 40 years. Mean duration of use of low dose aspirin was 22.23 ± 16.59 months. Lower gastrointestinal bleeding was noted in 81 (21.8%). Use of dose aspirin is significantly associated with lower gastrointestinal bleeding. Clinicians must anticipate adverse effects in such patients.